The Integration of Al-Farabi’s and Ibn Sina’s Philosophical Thought in Strengthening Islamic Literacy Culture - Nur Fadhilah Rusli; Indo Santalia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of classical Islamic thought has produced numerous prominent figures who played significant roles in shaping the civilization of knowledge. Among them are Al-Farabi and Ibn Sina, renowned as rationalist Muslim philosophers with major contributions to philosophy, logic, and Islamic epistemology. This paper aims to examine the integration of their intellectual ideas in strengthening Islamic literacy culture—namely, the culture of reading, writing, and critical thinking based on Islamic values. Using a qualitative approach grounded in library research, this article analyzes the relevance of the concepts of intellect, emanation, and education in the philosophies of Al-Farabi and Ibn Sina to the enhancement of literacy traditions in the modern era. The findings indicate that their philosophical thoughts can serve as a foundational framework for building a knowledgeable, ethical, and civilized society. This integration also emphasizes that literacy in Islam is not merely an intellectual activity but a form of worship that guides humans toward the perfection of reason and spirituality.